1984
DOI: 10.1161/01.hyp.6.2_pt_2.i183
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal hemodynamics and arterial pressure in aldosterone "escape".

Abstract: This study examined the importance of changes in renal hemodynamics and renal artery pressure (RAP) in allowing the kidneys to escape from the chronic sodium-retaining effects of aldosterone (Aldo). In five dogs in which RAP was permitted to increase during Aldo infusion (14 micrograms/kg/day), sodium excretion (UNaV) and fractional sodium excretion (FENa) decreased markedly on Day 1 and then returned to control on Days 2 to 4 of Aldo infusion as RAP and glomerular filtration rate (GFR) increased 15 to 19 mm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 0 publications
6
67
1
1
Order By: Relevance
“…In a 9-yr follow-up study, we showed that primary aldosteronism is characterized by partially reversible renal dysfunction (20), and demonstration that albuminuria is a marker of a hemodynamic rather than a structural renal defect has been reported also by Ribstein et al (19) in a short-term, postadrenalectomy evaluation of patients with adrenal adenoma. In agreement with the findings of studies that were conducted in more experimental settings (37)(38)(39), longitudinal studies consistently demonstrate that the hallmark of renal dysfunction in primary aldosteronism is reversible glomerular hyperfiltration that contributes to increase urinary albumin losses.…”
Section: Discussionsupporting
confidence: 84%
“…In a 9-yr follow-up study, we showed that primary aldosteronism is characterized by partially reversible renal dysfunction (20), and demonstration that albuminuria is a marker of a hemodynamic rather than a structural renal defect has been reported also by Ribstein et al (19) in a short-term, postadrenalectomy evaluation of patients with adrenal adenoma. In agreement with the findings of studies that were conducted in more experimental settings (37)(38)(39), longitudinal studies consistently demonstrate that the hallmark of renal dysfunction in primary aldosteronism is reversible glomerular hyperfiltration that contributes to increase urinary albumin losses.…”
Section: Discussionsupporting
confidence: 84%
“…17 Furthermore, it was shown that the infusion of aldosterone for 1 week to normotensive dogs determined a 20% to 24% increase of GFR, which was associated with an increase of renal perfusion pressure. 34 However, in the present study, GFR was slightly higher in PH than in PA patients with APA and IHA, both when raw and when covariate-adjusted GFR values were compared. Furthermore, we found a weak inverse significant relation (rϭϪ0.135; PϽ0.001) of GFR with UAE rate at univariate correlation, although this was not significant at multivariate analysis.…”
Section: Uae Rate In Pa and Ph Patientscontrasting
confidence: 69%
“…DOCA salt is a "prototype" model for salt-sensitive hypertension. 4 Secondary renin-angiotensin-aldosterone system suppression, 5 increased secretion of natriuretic peptides, 6 and altered pressure natriuresis 7 establish a new steady state between Na ϩ intake and Na ϩ excretion at a new blood pressure level. The kidneys escape the mineralocorticoid signal, and additional salt retention ceases, albeit with increased blood pressure.…”
mentioning
confidence: 99%